2009
DOI: 10.1038/nature08553
|View full text |Cite
|
Sign up to set email alerts
|

Common dependence on stress for the two fundamental laws of statistical seismology

Abstract: Two of the long-standing relationships of statistical seismology are power laws: the Gutenberg-Richter relation describing the earthquake frequency-magnitude distribution, and the Omori-Utsu law characterizing the temporal decay of aftershock rate following a main shock. Recently, the effect of stress on the slope (the b value) of the earthquake frequency-magnitude distribution was determined by investigations of the faulting-style dependence of the b value. In a similar manner, we study here aftershock sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(87 citation statements)
references
References 27 publications
9
78
0
Order By: Relevance
“…Furthermore, the role of the parameter b variations is critical. Strong variations of b across different stress regimes imply that this parameter acts as a stress meter that depends inversely on differential stress (e.g., Schorlemmer et al, 2005;Narteau et al, 2009, and references therein). Observations of seismic sequences have shown that b usually drops and becomes significantly lower in foreshocks than in aftershocks or in background seismicity (Papazachos, 1975;Jones and Molnar, 1979;Main et al, 1989;Molchan et al, 1999;Enescu et al, 2001;Nanjo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of the parameter b variations is critical. Strong variations of b across different stress regimes imply that this parameter acts as a stress meter that depends inversely on differential stress (e.g., Schorlemmer et al, 2005;Narteau et al, 2009, and references therein). Observations of seismic sequences have shown that b usually drops and becomes significantly lower in foreshocks than in aftershocks or in background seismicity (Papazachos, 1975;Jones and Molnar, 1979;Main et al, 1989;Molchan et al, 1999;Enescu et al, 2001;Nanjo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This can result in short-term variations of M c , which, if ignored, can lead to spurious results and misinterpretations (Kagan, 2004;Hainzl, 2013). Thus, a temporal resolution of M c is necessary to get unbiased parameter estimations of seismicity models such as the epidemic-type aftershock sequence (ETAS) model (Ogata, 1988;Zhuang et al, 2012) and to evaluate variations of statistical parameters such as the b-value (e.g., Imoto, 1991;Hainzl and Fischer, 2002;Mallika et al, 2013;Schurr et al, 2014;Huang and Beroza, 2015) or Omori c-value (e.g., Shcherbakov et al, 2004;Narteau et al, 2009;Davidsen et al, 2015). Both are important for physical interpretations and seismic-hazard estimations.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the result is more important, because it allows us to correlate the variation in the character of the aftershock activity with the maximum load because such a correlation is used [7] in the algorithm of earthquake prediction. However, our data require additional confirmation by tests on various materials that have different strengths, structures, and tendency to occurrence of aftershocks.…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%